Engineering Nature : Water, Development, and the Global Spread of American Environmental Expertise - Teisch, Jessica B. (Book collections on Project MUSE., 2011)
Focusing on globalization in the late nineteenth and early twentieth centuries, Jessica Teisch examines the processes by which American water and mining engineers who rose to prominence during and after the California Gold Rush of 1849 exported the United States' growing technical and environmental knowledge and associated social and political institutions. Teisch argues that by examining the successes and failures of various projects as American influence spread, we can see the complex role of globalization at work, often with incredibly disproportionate results.